2007
DOI: 10.1007/s00421-007-0483-y
|View full text |Cite
|
Sign up to set email alerts
|

Hematological response and diving response during apnea and apnea with face immersion

Abstract: Increased hematocrit (Hct) attributable to splenic contraction accompanies human apneic diving or apnea with face immersion. Apnea also causes heart rate reduction and peripheral vasoconstriction, i.e., a cardiovascular diving response, which is augmented by face immersion. The aim was to study the role of apnea and facial immersion in the initiation of the hematological response and to relate this to the cardiovascular diving response and its oxygen conservation during repeated apneas. Seven male volunteers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 20 publications
2
52
1
Order By: Relevance
“…These cardiovascular responses are obviously interplaying during water immersion and BH phases of SS routines due to intense exercise combined with BH, which would produce a rapid development of hypercapnia and hypoxia [35]. While apnea and facial immersion increase the parasympathetic tone causing HR reduction [34], [39], exercise increases sympathetic stimulation of the heart [3] and increases HR. So when the swimmer starts holding breath during the routines, both inputs compete with each other for control of HR [40] and O 2 flow to the exercising muscles, though the O 2 conservation diving response would finally prevail until the swimmer is able to breathe again.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cardiovascular responses are obviously interplaying during water immersion and BH phases of SS routines due to intense exercise combined with BH, which would produce a rapid development of hypercapnia and hypoxia [35]. While apnea and facial immersion increase the parasympathetic tone causing HR reduction [34], [39], exercise increases sympathetic stimulation of the heart [3] and increases HR. So when the swimmer starts holding breath during the routines, both inputs compete with each other for control of HR [40] and O 2 flow to the exercising muscles, though the O 2 conservation diving response would finally prevail until the swimmer is able to breathe again.…”
Section: Discussionmentioning
confidence: 99%
“…The economical use of O 2 results from lowered myocardial O 2 demands causing a decrease of the cardiac output [66]. It is well known that long-term apnea training increases hematocrit, erythropoietin concentration, hemoglobin mass, and lung volumes [39], [67], [68] indicating adaptation to hypoxia. An augmented diving response is associated with a reduced rate of arterial desaturation and a reduced rate of depletion of the lung O 2 stores during apnea at both rest and exercise, which is thought to reflect the O 2 -conserving effect of the human diving response [38], [43], [64], [69].…”
Section: Discussionmentioning
confidence: 99%
“…Linér and Linnarsson (1994) showed that the time constant for the recovery of CO 2 elimination was 27 s after breath holds lasting 75 s. This means that approximately 2 min (4 9 time constants) is enough to eliminate most of the excess CO 2 . In addition, we have shown that the venous PCO 2 returns to the preapneic level within 2 min after apneas in a series such as that in the present study (Schagatay et al 2007). These results speak against the possibility of any marked postapneic CO 2 retention under these conditions.…”
Section: Discussionmentioning
confidence: 57%
“…These variables were used for monitoring the safety of the subject during experiments and not included in subsequent analysis [for details concerning these variables under similar experimental conditions, see e.g. Schagatay et al (1999Schagatay et al ( , 2007]. Respiratory movements were measured with a pneumatic chest bellows, and recorded on a pen writer.…”
Section: Maximal-duration Apnea Seriesmentioning
confidence: 99%
“…The diving reflex, as a survival mechanism, is accompanied with an elevated arterial blood pressure though results are inconclusive [14,15]. The lack of oxygen due to apnea, inevitably triggers the anaerobic metabolism causing an increase in blood lactate [13,[16][17][18]. However, apnea trained individuals exhibit reduced blood acidosis and oxidative stress which may positively affect performance [17,19].…”
Section: Potential Benefits Of Hypoxic Training For Aquatic Sportsmentioning
confidence: 99%